2020
DOI: 10.1016/j.rbmo.2020.06.002
|View full text |Cite
|
Sign up to set email alerts
|

A 5-year multicentre randomized controlled trial comparing personalized, frozen and fresh blastocyst transfer in IVF

Abstract: Endometrial receptivityEndometrial receptivity analysis (ERA) Fresh embryo transfer (ET) Frozen embryo transfer (FET) Personalized embryo transfer (PET) Window of implantation (WOI)

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
142
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 137 publications
(144 citation statements)
references
References 22 publications
1
142
0
1
Order By: Relevance
“…EF and EB were collected following the previously described procedures (Vilella et al 2013; Simón et al 2020). Briefly, with the patient in the lithotomy position, the vagina and cervix were cleaned.…”
Section: Methodsmentioning
confidence: 99%
“…EF and EB were collected following the previously described procedures (Vilella et al 2013; Simón et al 2020). Briefly, with the patient in the lithotomy position, the vagina and cervix were cleaned.…”
Section: Methodsmentioning
confidence: 99%
“…Unscreened single vs. double blastocyst transfer resulted in equivalent live birth rates irrespective of age in another study [13]. On the other hand, other studies have shown increasing pregnancy rates transferring two as opposed to a single blastocyst [4,14]. The difference between the findings of these studies likely represents the role of endometrial receptivity, transfer technique, and embryo genetics [8,9].…”
mentioning
confidence: 92%
“…Although transferring multiple embryos may impact the pregnancy rate per transfer, multiple pregnancies remain a risk [4,6,14]. We have known that this is the desired outcome for many of our patients, with the opportunity of at one time to complete their family when two children are delivered as twins.…”
mentioning
confidence: 99%
“…The accuracy and reproducibility was proven to be reliable in subsequent studies [15][16][17]. Several studies have demonstrated that pregnancy outcomes of patients with RIF and infertile couples with conventional IVF [17,18] can be improved by personalized embryo transfer (pET) guided by the ERA test. In addition, relevant results indicate that transcriptomic and proteomic markers provide promising approaches for ER assessment.…”
Section: Introductionmentioning
confidence: 99%